Faculty Experiences of Merger and Organizational Change in a Social Work Program. Issue 1 (2nd January 2016) - Adedoyin, A. Christson; Miller, Monte; Jackson, Mary S.; Dodor, Bernice; Hall, Kristen
Abstract : Social work programs are experiencing unprecedented organizational changes due to budget cuts, dwindling resources, global, and technological challenges. However, there is limited information in the literature about the merger experiences of faculty in social work programs. On one hand undergoing merger and reorganization provides the opportunity to reorganize, reprioritize, re-assess, develop strategies, and explore previously untapped opportunities for social work programs. Conversely, merger experiences have caused frustration, intention to quit, confusion, and loss of professional identity for social work faculty. In this article the authors utilize a journaling method and sense-making approach of the merger experiences of some of the faculty members of a social work program in the United States. The authors suggest a framework to understand how the faculty confronted the challenges, overcame the pitfalls, and maximized the opportunities offered during the merger and organizational change process.